Peningkatan Keterampilan Menulis Cerita Pendek Melalui Metode Edutainment Dengan Media Kartu Pada Siswa Kelas VC SD Muhammadiyah 8 Jagalan Surakarta Tahun Ajaran 2015/2016 - Purbaningsih, Yuni Setyo (2016)
This study aims to improve the skills of writing a short story by applying methods of edutainment with media cards in class VC primary class Muhammadiyah 8 Jagalan Surakarta. This type of research is the PTK (Classroom Action Research). The subjects were students of class VC primary class 8 Muhammadiyah 8 Jagalan Surakarta totaling 28 students. Data was collected through interviews, observation and documentation. Test the validity using triangulation techniques and engineering resources. Data analysis was performed with 4 stages: data collection, data reduction, data presentation and conclusion. The results showed an increase in short story writing skills. This can be evidenced by the achievement indicators of short story writing skills as follows: Students are skilled to write a short story based on the elements of the story increased from 57.14% (prasiklus) to 92.85% (cycle II meeting II). Skilled students write a short story based on the spelling increased from 25% (prasiklus) to 82.14% (cycle II meeting II). Skilled students write a short story based on punctuation increased from 28.57% (prasiklus) to 82.14% (cycle II meeting II). Skilled students write a short story based on diction increased from 32.14% (prasiklus) to 92.85% (cycle II meeting II). The study concluded that the application of methods of edutainment with media cards can improve the skills of writing short stories in grade class VC Muhammadiyah 8 Jagalan Surakarta academic year 2015/2016.